(untitled) (Orchid Academia Siraha, 2023)
This paper explores the system of case marking in the Saptariya Tharu spoken in various districts of Nepal. Saptariya Tharu is identified as a nominative and accusative language, and studies are conducted to explore its case markers and postpositions. The paper discusses nominative case, accusative-dative case, locative case, genitive case, ablative case, instrumental case, and comitative case and highlights their use and examples. In addition, the paper compares the Sapataria Tharu case marking system with other Indo-Aryan languages spoken in Nepal’s Terai region. It points out that most languages in this region also have nomenclature-accusation patterns. Furthermore, this article notes the similarities between these languages, emphasizing the absence of ergative case markers and the differences between instrumental, genitive, dative, and locative markers. The research concludes that it reveals a rich case-marking system of Saptariya Tharu in a broader context of the Indo-Aryan languages spoken in Nepal’s terai region, highlighting its unique linguistic characteristics and typological similarities with neighboring languages.